PATHOGENETIC CONNECTIONS BETWEEN VARIOUS LINKS OF METABOLISM AND STRUCTURAL-FUNCTIONAL STATE OF THE HEART IN PATIENTS WITH СHD - Чекаліна, Наталія (SWorldJournal, 2023)
The article presents data reflecting the relationship between the indicators of the blood lipid spectrum, the functional state of the liver, hemocoagulation, chronic systemic inflammation, myocardial ischemia and the state of central hemodynamics in patie